2018
DOI: 10.4102/sajcd.v65i1.583
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study to determine the feasibility of a cluster randomised controlled trial of an intervention to change peer attitudes towards children who stutter

Abstract: BackgroundWhile randomised controlled trials (RCTs) are considered the gold standard of research, prior study is needed to determine the feasibility of a future large-scale RCT study.ObjectivesThis pilot study, therefore, aimed to determine feasibility of an RCT by exploring: (1) procedural issues and (2) treatment effect of the Classroom Communication Resource (CCR), an intervention for changing peer attitudes towards children who stutter.MethodA pilot cluster stratified RCT design was employed whereby the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…quintile group [lower versus higher] × intervention [CCR versus usual practice]). Subgroup analysis is supported by a previous study which showed schools behaving as clusters and as quintiles [ 20 ], while no large-scale findings have been reported. Treatment effect was additionally analysed in terms of the direction and magnitude.…”
Section: Methodsmentioning
confidence: 60%
See 2 more Smart Citations
“…quintile group [lower versus higher] × intervention [CCR versus usual practice]). Subgroup analysis is supported by a previous study which showed schools behaving as clusters and as quintiles [ 20 ], while no large-scale findings have been reported. Treatment effect was additionally analysed in terms of the direction and magnitude.…”
Section: Methodsmentioning
confidence: 60%
“…A stratified cluster randomised controlled trial (RCT) was conducted using a 1:1 allocation ratio whereby schools were the unit of randomisation and were stratified into two quintile groups (lower versus higher quintile groups). No changes were made to the methods after the trial commenced as a previous pilot study [ 20 ] guided this study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, researchers also learned that there were limitations in the procedural aspects of implementation which impacted negatively on the sensitivity of the protocol. Similarly, in case study 2, the pilot study [20] informed the design of an RCT through assessing the potential treatment effect of the CCR intervention as well as the feasibility of recruiting and retaining participants. The study concluded that an RCT was feasible subject to strengthening several procedural aspects of the process.…”
Section: Lesson 4: Pilot and Feasibility Studies Are A Critical Part ...mentioning
confidence: 99%